PENJATUHAN HUKUMAN TERHADAP PELAKU PROSTITUSI ONLINE DITINJAU DARI TINDAK PIDANA PERDAGANGAN ORANG (Studi Kasus Putusan Nomor 214/Pid.B/2021/PN.Gpr di Pengadilan Negeri Kabupaten Kediri) - Tustarama, Rekha; Nurbaedah, Nurbaedah (MIZAN, Jurnal Ilmu Hukum, 2023)
In this study, the sentencing of perpetrators of online prostitution is only for pimps, and for prostitutes and PSK users as witnesses, even though anyone who commits an unlawful act can be held accountable for their actions in order to provide a deterrent effect on the perpetrators. This is where problems arise because of someone committing an unlawful act or a criminal act, but in reality there is a legal vacuum in the substance of sentencing for CSWs and PSK Users. For anyone who violates or commits an unlawful act or a criminal act, especially online prostitution, which is clearly against the law, must be held criminally responsible with strict sanctions for those who commit these criminal acts. For this reason, in this study entitled "Sentence of Criminal Acts of Online Prostitution in terms of the Crime of Trafficking in Persons (Study on the case of decision number 214/Pid.B/2021/PN.Gpr at the District Court of Kediri Regency) with the formulation of the problem related to Criminal Liability of the Perpetrators (Pimps), PSK and Users of Online Prostitution PSK are reviewed from the Crime of Trafficking in Persons and the Judge's Considerations in deciding cases related to the sentencing of Pimps, CSWs, and Users of Online Prostitution PSK in terms of the Crime of Trafficking in Persons. This type of research uses Empirical Research with interviews. Data analysis uses an inductive method.The results of this study, criminal liability for perpetrators (pimps), prostitutes and users of online prostitution prostitutes are reviewed from the crime of trafficking in persons through the process of the Investigation Stage, Investigation Stage (witness examination, detention, confiscation, evidence), Prosecution Stage, and Trial Stage . Criminal liability for perpetrators (Pimps) of online prostitution here is as follows: Committing criminal acts, Capable of being responsible, There is no excuse for forgiveness. The judge's considerations in deciding cases related to the imposition of sentences against pimps, prostitutes, and users of online prostitution prostitutes are reviewed from the crime of trafficking in persons based on the indictment and cannot decide outside the indictment, namely considering because the elements fulfilled in the actions of the defendant article 296 of the Criminal Code, then the Defendant's actions must be declared legally and convincingly proven to have committed the crime as charged in the first indictment, then the sentence for the Defendant was sentenced to imprisonment for 1 (one) year and 4 (four) months; For actors who are also involved in online prostitution, such as prostitutes and PSK users, they are only witnesses in court. Regarding the non-regulation of the rules in the Law on Online Prostitution, it is necessary to have special regulations in the Criminal Code article 296 to regulate prostitution and entrapment for Commercial Sex Workers (PSK) and Users of Commercial Sex Workers (PSK) and Renewal of the Criminal Law regarding the imprisonment of criminal penalties can be imposed on Commercial Sex Workers (PSK) and PSK Users in order to have a deterrent effect for CSWs and PSK users.